Qualidade de vida no trabalho e saúde ocular ocupacional dos servidores técnicos administrativos das Universidades Federais do Brasil - Araujo, Sandra Aparecida de [UNIFESP] (2017)
Objective: The aims of the present study were the investigation, reflection and discussion of the quality of life and ocular occupational health on the job of employees at Federal Universities in Brazil. Method: Questionnaire containing 70 (seventy) objective questions covering diverse aspects related directly and indirectly to the humanistic aspect of administrative professional relationships was sent by mail to the Department of Personnel Management of 59 (fifty nine) Federal Universities in Brazil. The questionnaire also allowed participants to add complementary information, such as suggestions, criticisms and / or comments. The deadline established to finalize the receipt of questionnaires and initiate the interpretation of results corresponded to 60 (sixty) days from the date of shipment (06/02/2015). Results: A total of 26 (twenty-six) completed and signed questionnaires returned from all regions of Brazil, with reviews, suggestions and comments. The results suggest the need to discuss, evaluate and implement quality of life programs at work (QWT), taking into account the need to promote more humane environments. Conclusions: The data are an important instrument of reflection about the importance of information, prevention and the promotion health of and welfare of employees. In addition, the data indicate the relevance to implement actions and programs to promote the quality of working life and occupational eye health.